Benchmarking DNA methylation assays in a reef‐building coral. (14th November 2020) - Dixon, Groves; Matz, Mikhail
Abstract: Interrogation of chromatin modifications, such as DNA methylation, has the potential to improve forecasting and conservation of marine ecosystems. The standard method for assaying DNA methylation (whole genome bisulphite sequencing), however, is currently too costly to apply at the scales required for ecological research. Here, we evaluate different methods for measuring DNA methylation for ecological epigenetics. We compare whole genome bisulphite sequencing (WGBS) with methylated CpG binding domain sequencing (MBD‐seq), and a modified version of MethylRAD we term methylation‐dependent restriction site‐associated DNA sequencing (mdRAD). We evaluate these three assays in measuring variation in methylation across the genome, between genotypes, and between polyp types in the reef‐building coral Acropora millepora . We find that all three assays measure absolute methylation levels similarly for gene bodies (gbM), as well as exons and 1 Kb windows with a minimum Pearson correlation 0.66. Differential gbM estimates were less correlated, but still concurrent across assays. We conclude that MBD‐seq and mdRAD are reliable and cost‐effective alternatives to WGBS. The considerably lower sequencing effort required for mdRAD to produce comparable methylation estimates makes it particularly useful for ecological epigenetics.